Inhibition of p66Shc Oxidative Signaling via CA-Induced Upregulation of miR-203a-3p Alleviates Liver Fibrosis Progression - Zhecheng Wang; Yan Zhao; Huanyu Zhao; Junjun Zhou; Dongcheng Feng; Fan Tang; Yang Li; Li Lv; Zhao Chen; Xiaodong Ma; Xiaofeng Tian; Jihong Yao (Elsevier, 2020)
We previously found that inhibition of p66Shc confers protection against hepatic stellate cell (HSC) activation during liver fibrosis. However, the effect of p66Shc on HSC proliferation, as well as the mechanism by which p66Shc is modulated, remains unknown. Here, we elucidated the effect of p66Shc on HSC proliferation and evaluated microRNA (miRNA)-p66Shc-mediated reactive oxidative species (ROS) generation in liver fibrosis. An in vivo model of carbon tetrachloride (CCl4)-induced liver fibrosis in rats and an LX-2 cell model were developed. p66Shc expression was significantly upregulated in rats with CCl4-induced liver fibrosis and in human fibrotic livers. Additionally, p66Shc knockdown in vitro attenuated mitochondrial ROS generation and HSC proliferation. Interestingly, p66Shc promoted HSC proliferation via β-catenin dephosphorylation in vitro. MicroRNA (miR)-203a-3p, which was identified by microarray and bioinformatics analyses, directly inhibited p66Shc translation and attenuated HSC proliferation in vitro. Importantly, p66Shc was found to play an indispensable role in the protective effect of miR-203a-3p. Furthermore, carnosic acid (CA), the major antioxidant compound extracted from rosemary leaves, protected against CCl4-induced liver fibrosis through the miR-203a-3p/p66Shc axis. Collectively, these results suggest that p66Shc, which is directly suppressed by miR-203a-3p, is a key regulator of liver fibrosis. This finding may lead to the development of therapeutic targets for liver fibrosis.